Overcoming Pedagogical Conservatism in the Course of Innovative Educational Process in Educational Institutions - E Y Ibatullina; T V Vorontsova (Peoples' Friendship University of Russia (RUDN University), 2011)
In the article the problem of overcoming the conservatism and implementing the innovation process in the educational institution is revealed; the historical concepts of "conservatism", "innovation" are analyzed; the principles, the operational component and the organizational-pedagogical conditions of overcoming conservatism are defined.